Impact of work-family conflict on deviant workplace behavior through stress and burnout A sequential mediation model - Dr. Shazia Faiz; Um-e-Rubbab; Um-e-Rubbab (Journal of Business & Tourism, 2021)
Even though growing importance has been given to work-family conflict and deviant workplace behavior, the link between employees’ feelings of work-family conflict and deviant workplace behavior is still missing. To explain this mechanism the study examines sequential mediation through stress and burnout.It’sa time lag study; data were collected through self- reported questionnaires. For a sample of 147nurses at government hospitals in Pakistan structural equation modeling was conducted.The results revealed strong support for the hypothesized relationships. The findings indicate work-family conflict indirectly but positively associated with deviant workplace behavior, sequentially mediated first through stress and then burnout.The study connects the dots, four main workplace attitudes as variables of action, reaction, outcome, and consequence,and figures out how this mechanism works and WFC leads to burnout.Limitations of the study along with the future research directions are also discussed.